The Influence of Reward and Punishment on the IPAS Learning Outcomes of Fourth-Grade Students at SD Al Khotimah, Semarang City - Anissyam Etania Fajra; A.Y Soegeng Ysh; Asep Ardiyanto (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study aims to analyze the effect of implementing reward and punishment on the science learning outcomes (IPAS) of fourth-grade students at SD Al Khotimah, Semarang City. A quasi-experimental design using a nonequivalent control group model was employed, involving both control and experimental classes. Data were collected through pretest and posttest assessments. The findings reveal a significant difference between the two groups. The experimental class showed a posttest increase of 11.36 points, which was notably higher than the 4.15-point increase in the control class. The Independent Samples t-test produced a significance value of 0.024 < 0.05, confirming the significant effect of reward and punishment on students’ IPAS learning outcomes. The study concludes that these behavior reinforcement strategies effectively enhance students’ motivation, discipline, and academic performance in elementary school science learning.